Assessment of Metal Levels In Some Plants From Giresun - Mustafa Türkmen; Köksal Duran; Aysun Türkmen (Turkish Journal of Agriculture: Food Science and Technology)
The study performed the metal bioaccumulations in seven plant species from Giresun city. A total 140 specimens were collected from two stations (Station A; 40° 48’ N, 38° 19’ E, Station B; 50° 54’ N, 38° 26’ E) from March 2012 to September 2012. Plant samples were dissected, homogenized and dried at 105°C for 24 hours. An approximately 0.25 g sample of each plant leaf was digested with Cem Mars 5 microwave oven. After cooling, the residue was transferred to 50 ml volumetric flasks and diluted to level with deionized water. Before analysis, the samples were filtered through a 0.45 µm filter. All samples were analyzed (as mg kg-1 dry weight) three times for cobalt chromium, copper, iron, manganese, nickel, lead and zinc by ICP-MS. A logarithmic transformation was done on the data to improve normality. One way ANOVA and Duncan’s multiple range tests were performed to test the differences among metal levels of species. Concentrations of metals in the examined species ranged from 0.05 to 1.80 for cobalt, 0.14 to 3.24 for chromium, 2.33 to 28.1 for copper, 38.9 to 533 for iron, 1.81 to 64.6 for manganese, 0.81 to 18.9 for nickel, 0.32 to 6.22 for lead and 14.3 to 536 for zinc, in mg kg-1 respectively. Iron had the highest concentrations in all examined plant species in both stations except Zn for Sambucus ebulus in Station B. Second highest metal was zinc after iron. On the other hand, cobalt had lowest levels than other metals. The differences among metal levels in plant species were statistically significant. Maximum Provisional Tolerable Weekly Intakes (PTWI) in edible plant species were calculated.